2004
DOI: 10.1021/ja0486871
|View full text |Cite
|
Sign up to set email alerts
|

Osmabenzenes from the Reactions of HC≡CCH(OH)C≡CH with OsX2(PPh3)3 (X = Cl, Br)

Abstract: Treatment of OsX2(PPh3)3 (X = Cl, Br) with HCCCH(OH)CCH in THF produces OsX2(CH=C(PPh3)CH(OH)CCH)(PPh3)2, which reacts with PPh3 to give osmabenzenes [Os(CHC(PPh3)CHC(PPh3)CH)X2(PPh3)2]+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 15 publications
8
75
0
4
Order By: Relevance
“…10 We found that the reaction of OsCl 2 (PPh 3 ) 3 with readily accessible 1,4-pentadiyn-3-ol produced bisphosponium-substituted osmabenzene 3 at room temperature (Scheme 1). When PPh 3 was added to the reaction mixture, the isolated yield of 3 was increased from 44% to 75%.…”
Section: Osmabenzenementioning
confidence: 99%
“…10 We found that the reaction of OsCl 2 (PPh 3 ) 3 with readily accessible 1,4-pentadiyn-3-ol produced bisphosponium-substituted osmabenzene 3 at room temperature (Scheme 1). When PPh 3 was added to the reaction mixture, the isolated yield of 3 was increased from 44% to 75%.…”
Section: Osmabenzenementioning
confidence: 99%
“…A second pathway to stable osmabenzenes was reported by Jia and co-workers in 2004. [35] This group found that reaction of [OsCl 2 (PPh 3 ) 3 ] with 1,4-pentadiyn-3-ol led to the isolation of metallacycle 12, the phosphonium salt of an osmabenzene. The mechanism proposed for formation of this unusual species involves the substitution of a coordinated phosphine ligand with an h 2 -coordinated alkyne to give species 13 (Scheme 3).…”
Section: Osmabenzenesmentioning
confidence: 99%
“…[11] Although a number of metallabenzenes have been synthesized with p donors ortho to the metal fragment, [23,31] iridanaphthalene 107 and iridabenzenes 99, 105, and 115 are the first examples of metalla-aromatic species substituted with electron-withdrawing groups, namely CO 2 Me. Other examples of metallabenzenes bearing electron-withdrawing groups include the phosphonium-substituted osmabenzenes and ruthenabenzenes reported by Jia, [35,62] but these moieties are located on the less influential meta positions.…”
Section: Iridanaphthalenementioning
confidence: 99%
“…Until recently, only two families of discrete metallabenzenes were known, namely Ropers osmabenzenes (e.g., 1) [2] and Bleekes iridabenzenes (e.g., 2); [3] nonetheless, all investigations into both families originated from compounds 1 and 2, respectively. Very recent work on osmabenzenes [4] and irida-aromatic compounds [5] has provided a few additional examples; however, the generality of these methods has yet to be determined. Therein lies a key difficulty within this field of research: lack of versatile synthetic routes has meant that detailed, fundamental study of metallabenzenes has been problematic.…”
Section: Introductionmentioning
confidence: 99%